Naringenin inhibits human breast cancer cells (MDA-MB-231) by inducing programmed cell death, caspase stimulation, G2/M phase cell cycle arrest and suppresses cancer metastasis - Qi, Zhaozhen; Kong, Shuangxi; Zhao, Shunyu; Tang, Qiu (Cellular and Molecular Biology, 2021)
The current study was designed to unveil the anticancer effects of naringenin against breast cancer MDA-MB-231 cells. Cytotoxic effects were estimated via MTT viability assay. Clonogenic assay was performed to assess clonogenic potential of MDA-MB-231 cells. Apoptosis was examined via AO/EB staining, quantified via annexin V/PI staining and western blotting was performed to monitor apoptosis allied protein expressions. Cell cycle was analyzed through flow cytometric analysis. Transwell chambers assay was executed for determination of cell migration and cell invasion tendency of MDA-MB-231 breast cancer cells. Results indicated significant anticancer potential of naringenin drug against MDA-MB-231 cells. On evaluation of cell proliferation rate of breast cancer cells by MTT assay, it was observed that naringenin inhibited proliferation rate in dose as well as time dependent manner. AO/EB staining assay revealed potential morphological changes indicating apoptotic cell death. Annexin V/PI staining assay revealed increased apoptotic cell percentage with increased drug doses. The apoptosis inducing potential of naringenin drug was observed to be mediated via caspase activation. Flow cytometric analysis predicted cell cycle arrest at G2/M phase of cell cycle. Further cell migration as well as cell invasion tendency of MDA-MB-231 cells was reduced to minimum upon application of naringenin drug.